Education on the Behavior of Young Women Regarding the Risks of Early Pregnancy at Muhammadiyah High School in Serang City - partono siswosuharjo (STIKes RSPAD RSPAD Gatot Soebroto, 2024)
This research aims to provide education on the behavior of young women regarding the risks of early pregnancy at Muhammadiyah High School, Serang City in 2023. The type of research that will be used is analytical, quantitative, descriptive research. The population used is the sample size. In this study, the sample size was determined by total sampling. Researchers used a sample of 120 people. The results of this study conclude that there is a significant relationship between parenting styles and understanding the risk of pregnancy at a young age. There is a significant relationship between family communication patterns and understanding the risks of pregnancy at a young age. There is a significant relationship between parental education and understanding the risks of pregnancy at a young age. There is a significant relationship between family form and understanding the risk of pregnancy at a young age. Parental parenting styles have the greatest influence on young women in understanding the risk of pregnancy at a young age, namely with an F value of 143.431. Family form has the smallest influence (F = 4.150) for young women in understanding the risk of pregnancy at a young age.